Metode Pembelajaran yang Disarankan untuk SD dalam Menerapkan Pembelajaran Abad 21 pada Muatan IPS - Mevi Tasya Mevlevi; Susan sri Nurani; Susan Sri Nurani; Muh Husen Arifin (Universitas Indraprasta PGRI Jakarta, 2022)
Social studies education in elementary schools is applied by taking into account the characteristics of students' thinking abilities which are still overall. Social studies education as a way of education is applied to the form of subjects applied in the educational curriculum. Social studies learning in elementary school consist of several social science concepts, one of which is history. However, during the current pandemic, online learning, students tend to be individualistic because the ongoing learning process is less monitored and students only accept and do assignments, so that they are not enhanced in aspects of skills and attitudes such as collaboration and communication, so learning can be said to be less effective. In this way, it is conducted research using a literature study method by reading research results and observations at elementary schools in Bandung in 2021 such as reviewing direct learning. In the current conditions there are results that the methods applied by teachers, are important to influence the learning process and outcomes. One of them is to overcome these problems by using the right one according to the needs of students and combining it with the application of the characteristics of 21st century learning, namely 4C to adjust the situation of students and the skills that students need to master. So this paper discusses the importance of learning and the application of 21st century learning social studies in elementary school.